The impact of human resource strategy to knowledge process in the Malaysian electrical and electronics firms - Yousif Mamoun; Syed Azizi Wafa; Ramraini Ali Hassan (Asian Academy of Applied Business, 2018)
The purpose of this paper is to identify the impact of HR strategy to knowledge process in the Malaysian electrical and electronics firms. Because of the importance of electrical electronics firms to Malaysian economy, the objectives investigate the impact of human resource strategy, knowledge process in this sector. This paper conducted a quantitative approach using, a questionnaire with five points Likert scale. The respondents of this study consist of 287 managers from electrical and electronics firms across Malaysian states including Kuala Lumpur, Selangor, Penang, Johor, Kedah, and Melaka, Sabah, Sarawak. The list from the Federation of Malaysian Manufacturers (FMM) indicated that most of firms were located in these states. Statistical package for social science was used to generate the descriptive statistics besides the Partial least squares structural equation modeling (PLS SEM) as the statistical instrument to examine the measurement model and structural model. Results confirmed that, human resource strategy is significant to knowledge process (acquisition, conversion, application, protection) in the Malaysian electrical and electronics firms. Based on the results, the HR strategy adopted by a firm has a significant effect and can be a strong predictor of the knowledge. Some guidelines are suggested for top management and decision makers in electrical and electronics firms on how to encourage the application of human resource strategy that enhances the level of knowledge and skills, besides developing appropriate behavior. Eventually, management and decision makers would identify the necessary steps on how to encourage and generate knowledge in their organizations.